Disease burden of mild asthma in China. Issue 4 (20th October 2017) - Ding, Bo; Small, Mark
Abstract: Background and objective: The impact, treatment patterns and control of mild asthma are poorly understood for Chinese patients. This study describes the characteristics, therapeutic interventions and burden of mild asthma on patients residing in major cities of China. Methods: The Respiratory Disease Specific Program 2015, a cross‐sectional survey, was conducted with Chinese physicians and their patients. The survey assessed clinical characteristics, asthma symptoms, exacerbations, rescue inhaler usage, treatment adherence, asthma control, work and activity impairments and healthcare utilization for patients prescribed Global Initiative for Asthma (GINA) Step 1 or 2 treatment defined mild asthma. Results: From a total sample of 988 patients, 229 patients met the criteria for mild asthma, with 25.3% classified as Step 1 and 74.7% as Step 2. Overall, 12.6% of patients were considered of high adherence to prescribed treatment. Physicians reported that 75% of patients overall were well controlled, although well‐controlled asthma as defined by GINA was achieved in only 14.2% of patients. 26.5% of patients indicated daily use of as‐needed rescue medication in the last 4 weeks. 17.8% of patients experienced ≥1 exacerbations in the last 12 months and impaired work productivity was 27.2% overall. Conclusion: Less than 15% of patients were well controlled according to GINA criteria despite physicians reporting the majority of patients were well controlled. Over one‐fourth of patients relied on daily rescue inhaler medication, while exacerbation frequency and work and activity impairment were higher than might reasonably be expected in a mild asthmatic population. Abstract : See related Editorial This observational study of Chinese patients with mild asthma reveals that physicians considered 75% to be well or completely controlled, although only 14.2% were well controlled according to the Global Initiative for Asthma criteria. Treatment adherence was low, and many patients experienced nocturnal symptoms, exacerbations and work and activity impairments.